Managing Religious Tension: MUI, Legitimacy, and Urban Conflict Resolution - Susilawati; Siti Fuadah; Mia Fitriah Elkarimah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Religious conflict in Indonesia does not always stem from doctrinal differences, but often arises from issues of communication, governance, public perception, and social relations within heterogeneous urban spaces. This study aims to analyze the intervention of the Indonesian Ulema Council in the conflict involving Majelis Taklim Umi Cinta in Bekasi City Indonesia, with a focus on how MUI exercised its authority in resolving a non-doctrinal religious conflict. This research employed a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews with MUI administrators, local government officials, Islamic religious counselors, community leaders, reporting residents, and the leader of the study group, as well as through document analysis of MUI decrees, mediation records, media reports, and activity documentation. The data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing and verification. The findings show that the conflict was not primarily caused by doctrinal deviation, but by miscommunication, media framing, environmental disturbance, and weak governance of a non-formal religious assembly. The study also finds that MUI’s authority operated effectively through tabayyun, mediation, and cross-institutional coordination based on moral legitimacy rather than legal coercion. The implication of this research is that religious authority in contemporary Indonesia should be understood not only as a guardian of doctrine, but also as a form of social mediation in managing public perception, religious governance, and coexistence in heterogeneous communities. Konflik keagamaan di Indonesia tidak selalu berakar pada perbedaan doktrin, tetapi kerap muncul dari persoalan komunikasi, tata kelola, persepsi publik, dan relasi sosial dalam ruang perkotaan yang heterogen. Penelitian ini bertujuan menganalisis intervensi Majelis Ulama Indonesia dalam konflik yang melibatkan Majelis Taklim Umi Cinta di Kota Bekasi Indonesia, dengan fokus pada cara MUI menjalankan otoritasnya dalam menyelesaikan konflik keagamaan yang bersifat non-doktrinal. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus deskriptif. Data dikumpulkan melalui wawancara mendalam dengan pengurus MUI, aparatur pemerintah setempat, penyuluh agama, tokoh masyarakat, warga pelapor, dan pimpinan majelis taklim, serta melalui analisis dokumen seperti surat keputusan MUI, notulen mediasi, laporan media, dan dokumentasi kegiatan. Data dianalisis menggunakan model interaktif Miles dan Huberman melalui reduksi data, penyajian data, serta penarikan dan verifikasi kesimpulan. Hasil penelitian menunjukkan bahwa konflik yang terjadi tidak terutama disebabkan oleh penyimpangan akidah, melainkan oleh miskomunikasi, framing media, gangguan lingkungan, dan lemahnya tata kelola majelis taklim non-formal. Penelitian ini juga menemukan bahwa otoritas MUI bekerja secara efektif melalui tabayyun, mediasi, dan koordinasi lintas institusi berbasis legitimasi moral, bukan paksaan hukum. Implikasi penelitian ini menunjukkan bahwa otoritas keagamaan di Indonesia kontemporer perlu dipahami tidak hanya sebagai pengawas doktrin, tetapi juga sebagai mediator sosial dalam mengelola persepsi publik, tata kelola keagamaan, dan koeksistensi di Masyarakat heterogen.